2022
DOI: 10.1039/d1dt03931h
|View full text |Cite
|
Sign up to set email alerts
|

CeO2 decorated bimetallic phosphide nanowire arrays for enhanced oxygen evolution reaction electrocatalysis via interface engineering

Abstract: To realize electrocatalytic water splitting for hydrogen production, the development of efficient and durable anode materials containing earth-abundant elements is of great significance. In this work, we demonstrate a novel...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…As shown in Figure 2d, peaks at 886.4 and 904.6 eV are attributed to the Ce 3+ , while the peaks at 883.2, 888.2, 894.4, 901.8, 906.9, and 911.8 eV are assigned to the Ce 4+ . [ 26 ] As for the Co 2p core level, the peaks at 778.3 and 793.2 eV are indexed to CoP bonds in CoP/Ni 3 P, while the peaks at 782.2 and 798.1 eV originated from surface oxides. [ 27 ] After doping with Ce, the peaks at 778.9 and 793.8 eV are indexed to CoP bonds in Ce 0.2 ‐CoP/Ni 3 P, which show an apparent shift of 0.6 eV as compared with CoP/Ni 3 P, indicating a charge transfer from CoP/Ni 3 P to Ce.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 2d, peaks at 886.4 and 904.6 eV are attributed to the Ce 3+ , while the peaks at 883.2, 888.2, 894.4, 901.8, 906.9, and 911.8 eV are assigned to the Ce 4+ . [ 26 ] As for the Co 2p core level, the peaks at 778.3 and 793.2 eV are indexed to CoP bonds in CoP/Ni 3 P, while the peaks at 782.2 and 798.1 eV originated from surface oxides. [ 27 ] After doping with Ce, the peaks at 778.9 and 793.8 eV are indexed to CoP bonds in Ce 0.2 ‐CoP/Ni 3 P, which show an apparent shift of 0.6 eV as compared with CoP/Ni 3 P, indicating a charge transfer from CoP/Ni 3 P to Ce.…”
Section: Resultsmentioning
confidence: 99%
“…Here, Qu et al reported amorphous IrO x / CeO 2 nanowires as highly active and acid-resistant OER catalysts by a simple electrospinning/calcination method. 152 The amorphous catalyst has a high quality activity of 167 160 These two Ce(IV) oxide based electrocatalysts GDC and SDC showed excellent activity in OER and HER, respectively. GDC/NF shows good OER performance, achieving current density of 10 and 100 mA cm À2 at the overpotential of 300 and 420 mV.…”
Section: Oxygen Evolution Reactionmentioning
confidence: 99%
“…Based on this, Li et al developed a novel heterostructure that facilitates the deposition of CeO 2 NPs on the surface of MOF-derived Co 0.4 Ni 1.6 P nanowire arrays, an interface engineering strategy that triggers the formation of abundant oxygen sites and provides more electrocatalytic active sites. 167 In addition, synergies in the composite can regulate the electronic structure, thereby enhancing charge transfer capabilities. Thanks to these advantages, the heterostructure exhibits remarkable OER electrocatalysis in 1.0 M KOH electrolyte, requiring 268 and 343 mV overpotentials to produce current densities of 10 and 100 mA cm À2 , with a low Tafel slope of 79.3 mV dec À1 , respectively.…”
Section: Oxygen Evolution Reactionmentioning
confidence: 99%
“…Cong et al developed a Co 0.4 Ni 1.6 P‐CeO 2 heterostructure and found that it could drive a current density of 100 mA cm −2 at an overpotential of 345 mV in solution of 1 m KOH + 0.5 m NaCl. [ 168 ] The experimental and theoretical investigations revealed that the heterostructure could optimize the electronic structure of Co 0.4 Ni 1.6 P‐CeO 2 , leading to a charge redistribution and a generation of a large number of oxygen vacancies. Furthermore, according to ultraviolet photoelectron spectroscopy (UPS) measurements, the d ‐band center of Co 0.4 Ni 1.6 P was uplifted after interaction with CeO 2 , and the work function ( W f ) of Co 0.4 Ni 1.6 P‐CeO 2 was lower than that of Co 0.4 Ni 1.6 P, indicating its higher interfacial charge transfer efficiency.…”
Section: Designing Strategies Toward Improved Oer Selectivity and Chl...mentioning
confidence: 99%